The Vocabulary and Moments of Change: Thucydides and Isocrates on the Rise and Fall of Athens and Sparta - Bartzoka, Alexandra (Pnyx: Journal of Classical Studies, 2022)
This paper presents the events classical authors deemed as key moments in the rise and fall of Athens and Sparta, and examines the vocabulary they used to describe change: its extent (momentary or long-lasting), nature (evolution, transition, reversal, destruction, renewal), and effects (positive or negative). The Persian Wars, the end of the Peloponnesian War, and the battles of Cnidus, Naxos, and Leuctra were frequently thought of as the causes of Athens’ and Sparta’s growth or collapse, prosperity or misfortune. Τhese events were not only key moments in the balance of power in interstate relations, but also part of a particular argumentation which exploited and presented the phenomenon of change in several ways and through varying narratives. The study of the vocabulary pertaining to the rise and fall of the two cities reveals, on the one hand, the different ways one can treat change and, on the other hand, that the relevant words can convey neutral, positive or negative connotations, depending especially on an author’s intentions when emphasising a particular event.